2017
DOI: 10.1038/s41565-017-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiative control of dark excitons at room temperature by nano-optical antenna-tip Purcell effect

Abstract: Excitons, Coulomb-bound electron-hole pairs, are elementary photo-excitations in semiconductors that can couple to light through radiative relaxation. In contrast, dark excitons (X) show anti-parallel spin configuration with generally forbidden radiative emission. Because of their long lifetimes, these dark excitons are appealing candidates for quantum computing and optoelectronics. However, optical read-out and control of X states has remained challenging due to their decoupling from light. Here, we present a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
274
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(284 citation statements)
references
References 40 publications
9
274
0
1
Order By: Relevance
“…Monolayer WSe2 hosts a rich spectrum of excitonic species [23][24][25][26][27][28] . Several previously identified excitonic states are indicated in the figure, including the neutral bright exciton ( 0 ), bright trions ( ± ) [29][30][31][32][33] , the intravalley spinforbidden dark exciton ( 0 ) 17-20, 34 , and dark trions ( ± ) 18, 35 . The recently identified zone-center Γ 5or ′′phonon replicas below both neutral ( Γ 5 0 ) 12,13 and charged dark excitons ( Γ 5 ± ) 12 are also resolved, as indicated by black arrows.…”
Section: Maintextmentioning
confidence: 99%
“…Monolayer WSe2 hosts a rich spectrum of excitonic species [23][24][25][26][27][28] . Several previously identified excitonic states are indicated in the figure, including the neutral bright exciton ( 0 ), bright trions ( ± ) [29][30][31][32][33] , the intravalley spinforbidden dark exciton ( 0 ) 17-20, 34 , and dark trions ( ± ) 18, 35 . The recently identified zone-center Γ 5or ′′phonon replicas below both neutral ( Γ 5 0 ) 12,13 and charged dark excitons ( Γ 5 ± ) 12 are also resolved, as indicated by black arrows.…”
Section: Maintextmentioning
confidence: 99%
“…The spin-forbidden dark exciton, nonetheless, can also radiate through a finite out-ofplane dipole moment, which does not obey the same valley physics as the bright exciton, which arises from the combination of the inversion symmetry breaking and three-fold rotation symmetry that restricts the in-plane dipole radiation. 28,33 . As a result, we previously found that the valley-resolved PL spectra under an out-of-plane magnetic field exhibit a unique "cross" pattern in the intrinsic regime, distinctively different from other excitonic complexes [29][30][31] .…”
Section: Main Textmentioning
confidence: 99%
“…In the inhomogeneous plasmonic cavity,t he molecular dipole experiences driving forces from its own field, which is the field that arrives back to the molecules after scattering by the cavity.T his self-interaction results in ad ressing of the molecular excited states,l eading to ap erturbation of the complex eigenfrequencies of the states.V ariations in the real part of eigenfrequencies reflect the energy shift of the observed emission frequency, known as the Lamb shift; [21] while the change of the imaginary part leads to the modifications of the decay rate,i dentified as the Purcell effect. [22] Here we focus on the Lamb shift effect, the energy shift Dw / ÀRe m Gr ; r 1 ; w ðÞ m ðÞ ,i nw hich m is the molecular dipole moment and Gr ; r 1 ; w ðÞ is the Greensfunction of the molecule-cavity system. This relation thus directly links the observed random frequency shifts to the molecular dynamics,f or example,r eflecting the random rotation or motion of molecules in the nanocavity.…”
mentioning
confidence: 99%